2018
DOI: 10.1016/j.ihj.2018.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Is C-peptide a predictor of severity of coronary artery disease in metabolic syndrome? An observational study

Abstract: BackgroundVarious cardiovascular disease (CVD) risk factors have been implicated to correlate with the severity of the disease. Present study was conducted to correlate one such risk factor i.e. fasting serum C-peptide with the presence or absence and the severity of CVD in Indian population.Methods68 patients with metabolic syndrome who underwent coronary angiogram for suspected CVD were included. Their fasting serum C-peptide levels were measured in addition to routine biochemical and cardiological tests. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Moreover, fold changes of C-peptide during an OGTT were inversely associated with those of FGF21 in individuals with normal glucose tolerance (35), and FGF21 related signal pathways played important roles in the progression of NAFLD (36). In addition, previous studies have indicated that C-peptide may be also a predictive marker of the severity of the cardiovascular disease (37) and mortality (38), which suggested C-peptide was a bioactive peptide with other potential physiological functions. Thus, AUC CP may partly mediate the association between SUA/Cr and NAFLD via insulin resistance and other potential physiological function.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, fold changes of C-peptide during an OGTT were inversely associated with those of FGF21 in individuals with normal glucose tolerance (35), and FGF21 related signal pathways played important roles in the progression of NAFLD (36). In addition, previous studies have indicated that C-peptide may be also a predictive marker of the severity of the cardiovascular disease (37) and mortality (38), which suggested C-peptide was a bioactive peptide with other potential physiological functions. Thus, AUC CP may partly mediate the association between SUA/Cr and NAFLD via insulin resistance and other potential physiological function.…”
Section: Discussionmentioning
confidence: 99%
“…(1) diagnosis of secondary hypertension (n � 106), (2) diagnosis of diabetes mellitus (n � 493), (3) severe arrhythmia (n � 34), (4) moderate to severe kidney dysfunction (estimated glomerular filtration rate (eGFR) ≤60 ml min −1 1.73 m 2 ) (n � 122), ( 5) left ventricular systolic dysfunction (LVEF <50%) (n � 58), (6) severe valvular heart disease (n � 26), (7) peripheral vascular diseases (PAD) (n � 62), ( 8) myocardial infarction or unstable angina pectoris (n � 156), and (9) those subjects missing dates of baPWV or C-peptide (n � 213). Finally, the present study contained a total of 730 subjects.…”
Section: Study Subjectsmentioning
confidence: 99%
“…C-peptide is cosecreted with insulin on an equimolar basis; this is more stable, has fewer influencing factors, and can better reflect the secretion ability of overall and residual islet ß-cell [4][5][6]. In addition, C-peptide may also be a predictive marker of the severity of cardiovascular disease [7] and mortality [8]; the research suggests that C-peptide is a bioactive peptide with other potential physiological functions. Meanwhile, the detection of C-peptide is simple and convenient.…”
Section: Introductionmentioning
confidence: 99%
“…obesity characteristics) (Andrade et al, 2018). Gradually, C-peptide values have come to be considered as crucial for possible correlation with the circumstances of cardiovascular diseases (Harnishsingh and Rama, 2018).…”
Section: Introductionmentioning
confidence: 99%